2022
DOI: 10.1021/jacs.2c05787
|View full text |Cite
|
Sign up to set email alerts
|

Unique Electrical Signature of Phosphate for Specific Single-Molecule Detection of Peptide Phosphorylation

Abstract: Single-molecule measurements of biomaterials bring novel insights into cellular events. For almost all of these events, post-translational modifications (PTMs), which alter the properties of proteins through their chemical modifications, constitute essential regulatory mechanisms. However, suitable single-molecule methodology to study PTMs is very limited. Here we show single-molecule detection of peptide phosphorylation, an archetypal PTM, based on electrical measurements. We found that the phosphate group st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Thus, technologies used for their detection at the single-molecule level are in high demand. 152,153 For example, two major PTMs, phosphorylation and glycosylation, are important regulatory processes, but have also been implicated in pathogenic pathways of many diseases, such as diabetes, cancer, and Alzheimer's. 154,155 Joo and Dekker et al 156 demonstrated a proof-of-principle for the label-free differentiation of both phosphorylation and O-glycosylation, and their mutual discrimination from unmodified peptides, using a FraC nanopore and a model peptide, modified at a serine site with either of these PTMs (Figure 3g).…”
Section: Profiling and Identifying Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, technologies used for their detection at the single-molecule level are in high demand. 152,153 For example, two major PTMs, phosphorylation and glycosylation, are important regulatory processes, but have also been implicated in pathogenic pathways of many diseases, such as diabetes, cancer, and Alzheimer's. 154,155 Joo and Dekker et al 156 demonstrated a proof-of-principle for the label-free differentiation of both phosphorylation and O-glycosylation, and their mutual discrimination from unmodified peptides, using a FraC nanopore and a model peptide, modified at a serine site with either of these PTMs (Figure 3g).…”
Section: Profiling and Identifying Peptidesmentioning
confidence: 99%
“…PTMs of proteins constitute an essential regulatory mechanism involved in almost all cellular events. Thus, technologies used for their detection at the single-molecule level are in high demand. , For example, two major PTMs, phosphorylation and glycosylation, are important regulatory processes, but have also been implicated in pathogenic pathways of many diseases, such as diabetes, cancer, and Alzheimer’s. , Joo and Dekker et al demonstrated a proof-of-principle for the label-free differentiation of both phosphorylation and O-glycosylation, and their mutual discrimination from unmodified peptides, using a FraC nanopore and a model peptide, modified at a serine site with either of these PTMs (Figure g). The experiments in this work employ a model system with bespoke peptides designed to be simple, yet they present an important initial step in demonstrating the feasibility of PTM recognition at the single-molecule level using biological nanopore sensors.…”
Section: Profiling and Identifying Peptidesmentioning
confidence: 99%
“…The proposed applicability for studying such systems is to develop biochemical sensors, since their electronic responses are expected to vary in accordance with changes in their immediate environment, which can have wide applicability in pathogen and toxic detection in futuristic devices. [23][24][25][26] Porphine has been found to coordinate with various transition metal ions (metalloporphyrins), which affects the electron transport through the overall system, as theoretically established by Shuai et al [27] and Wang et al [28] The electronic behavior has also been theoretically considered in various geometric forms, such as tapes, [29] wires, [30,31] and sheets. [32] The effect of donoracceptor groups on the electron transport behavior of porphyrin DOI: 10.1002/pssr.202300431 Electronic conductance through a single molecule is sensitive to its structural orientation between two electrodes, owing to the distribution of molecular orbitals and their coupling to the electrode levels, that are governed by quantum confinement effects.…”
Section: Introductionmentioning
confidence: 97%
“…The proposed applicability for studying such systems is to develop biochemical sensors, since their electronic responses are expected to vary in accordance with changes in their immediate environment, which can have wide applicability in pathogen and toxic detection in futuristic devices. [ 23–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule transport experiments are gaining importance as a tool to monitor chemical reactions at the single-molecule level and in the chemical and biological sciences in general. For example, in cases where the analyte has a low junction formation probability, the overabundance of blank traces can obscure the molecular signal from the analyte.…”
Section: Introductionmentioning
confidence: 99%